Fighting for Uyghur Rights (American Journal of Islam and Society, 2006)
I begin my brief story in the 1960s, when many Uyghur (also spelled“Uygur” and “Uighur”) people, including myself, struggled against starvation.The already difficult lives of Uyghurs living in East Turkestan1 (alsoknown as the Xinjiang Uyghur Autonomous Region [XUAR]) under Chinesegovernment rule became much worse during the Cultural Revolution.Everything was rationed and controlled by the government and food was invery short supply. There was no private enterprise. Trying to find any way Icould to alleviate the poverty we were suffering, I started to make and sellchildren’s clothes. I also took in laundry to earn some money. From there, Ibegan to travel to different cities (first within East Turkestan and laterthroughout China) buying fabrics and garments and selling them on thestreet. Of course, this was not allowed under the communist system, andmany times the Chinese police confiscated all of my goods and charged mewith “taking the road of the capitalists.” Nor was it usual for a woman totravel in the region. I endured many hardships and indignities, but I wasdetermined to care for my children and improve my life.During the 1980s, as China began its economic reforms, I was able toset up a small store to do business in Urumchi, the capital of East Turkestan,and gradually started to prosper. I always tried to encourage the otherUyghur street sellers and merchants as well. In March 1987, I established the“Eighth of March” market (named in honor of International Women’s Day),a covered marketplace that housed ninety-three stores and stands. In 1989, Ibuilt a seven-story apartment building, and a few years later I built theRebiya Kadeer Department Store in downtown Urumchi. The Uyghur streetvendors could come and sell their goods in my store. At some point in mystruggle for economic independence, I became one of the ten richest peoplein China, for my business eventually grew into a multi-million dollar tradingcompany ...